Evaluating the factors affecting dairy commodity returns: the case of European dairy markets - Staugaitis, Algirdas Justinas; Christauskas, Česlovas (Business, Management and Economics Engineering, 2025)
Purpose – motivated by the price spikes and booms in major commodities markets around the world, this study looks into the factors that affect the variance in returns from dairy futures contracts. The purpose of the study is to determine whether dairy commodity prices – especially in times of economic turmoil – are being driven away from their fundamental value. The study focuses on European dairy futures markets, which are less studied by other authors in their research and are at a nascent stage of development in comparison to other agricultural commodity markets. The study includes various determinants such as energy prices, major stock indices, as well as market related variables such as financial speculation, in order to test whether returns from dairy commodities can be explained solely by macroeconomic factors or if this impact is amplified by trade volume or financial speculation within these markets. Therefore, the paper aims to assess the determinants of dairy futures prices before and after 2020, when the COVID-19 pandemic began and was followed by the war in Ukraine.Research methodology – the authors analyse dairy commodities traded on the European Energy Exchange (EEX) and employ the generalised autoregressive conditional heteroskedasticity (GARCH) modelling, as well as the Augmented Dickey-Fuller (ADF) and Granger non-causality tests to analyse what drives the returns from dairy commodity futures and the direction of this impact. The study consists of two-time frames: before and after the COVID-19 pandemic. Findings – an important finding from the study is that returns from dairy commodities are mostly explained by macroeconomic variables when analysing the post-2020 timeframe. Dairy commodities also experience asymmetric return volatility, showing that in dairy markets, negative returns are followed by reduced volatility. However, the role of trade volume or financial speculation on dairy commodity returns is found to be mixed or that it has an effect only on butter commodities when analysing 2020 and onward time period. Another important finding is that only returns from skimmed milk futures are significantly affected by seasonality. Research limitations – the study uses only two dairy commodity types in the research, there is insufficient data on non-commercial positions from EEX. Practical implications – as dairy commodities markets grow and attract more market activity, regulators should be more careful about geopolitical risks and financial speculation in European dairy futures markets.Originality/Value – the study examines European dairy futures markets, which are relatively new compared to other commodity markets and have not received as much attention in other research.